Analysis of the Effect of Virtual Reality Training on Improving Employee Soft Skills in the Digital Era - Zeanette T Lisbet; Samantha Gonzales (Yayasan Adra Karima Hubbi, 2025)
Background. The digital age has prompted organizations to develop a training approach that focuses not only on technical skills, but also soft skills such as communication, collaboration, and leadership. Virtual Reality (VR) is emerging as a promising training medium due to its ability to create immersive and realistic learning experiences. Purpose. This study aims to analyze the influence of Virtual Reality-based training on improving employees' soft skills in a digital work environment. Method. This study uses a quantitative approach with a quasi-experimental design of the non-equivalent control group design. The sample consisted of 60 employees who were divided into two groups, namely experimental (VR) and control (conventional training). Data collection was carried out through pretest and posttest using standardized interpersonal skills instruments. Results. The results of the analysis showed that there was a significant improvement in the experimental group compared to the control group. Interactive simulations through VR have succeeded in improving the aspects of communication, leadership, and teamwork more evenly and in-depth. Conclusion. VR-based training has proven to be effective as a medium for developing employees' soft skills. This technology is able to provide a learning environment that is relevant to the needs of today's world of work and contributes to the transformation of human resource training methods.